An Advanced Review on Pharmacology and Phytochemistry of Folklore Medicinal Plant Hyptis suaveolens (L.) Poit - Priya, M. Devi (Cutting-edge Research in Agricultural Sciences Vol. 12, 2021)
The Lamiaceae family includes Hyptis suaveolens (L.) Poit. (Bush mint). It's an invasive weed with insecticidal properties. It has traditionally been used to treat lung infections, uterine infections, and skin problems. Phytochemicals isolated from the plant, including as steroids, alkaloids, phenolics, flavonoids, tannins, glycosides, and essential oil, have medical and pharmacological use . The current review paper focuses on the H. suaveolens pharmacological and other relevant elements.